Association between removable prosthesis-wearing and pneumonia: a systematic review and meta-analysis - Tong Wah Lim; Kar Yan Li; Michael Francis Burrow; Colman McGrath (BMC, 2024)
Abstract Background A high burden of respiratory pathogens colonizing removable prosthesis surfaces suggests the potential of association between removable prosthesis-wearing and respiratory infections. Therefore, this systematic review and meta-analysis aimed to evaluate the evidence from clinical studies concerning the association between removable prosthesis-wearing and respiratory infections. Methods Clinical studies that reported respiratory infections associated with adult patients wearing removable prostheses in any centers (hospitals and nursing homes) or communities were included. Literature was searched across five electronic databases (MEDLINE, Cochrane Library, EMBASE, Web of Science, and Scopus) to 28 May 2024. An additional search was performed for unpublished trials and references cited in related studies. The Newcastle-Ottawa Scale was employed for the quality assessment. The certainty assessment was established using GRADE. The results were pooled using a frequentist random-effects meta-analysis and the odds ratios generated. Results A total of 1143 articles were identified. Thirteen articles had full-text articles screening and an additional two articles were added through reference linkage. Ultimately, six non-randomized clinical studies reporting various types of pneumonia contributed to this review. Overall odds of having pneumonia among prosthesis wearers were 1.43 (95% CI: 0.76 to 2.69) and 1.27 (95% CI: 1.11 to 1.46) using the random- and fixed-effects models, respectively. The heterogeneity in the meta-analysis was substantial. In subgroup analysis according to the study design, the heterogeneity within prospective studies was much reduced, I2 = 0% (p = 0.355). The certainty of the evidence evaluated using the GRADE approach was low to very low evidence for prosthesis wearers developing pneumonia based on studies. Conclusions There was no conclusive evidence from the non-randomized clinical studies supporting whether prosthesis-wearing is a risk factor for pneumonia based on outcomes from this review.